Evaluation of fish image analysis system on assessing her2 amplification in breast carcinoma cases - Kasampalidis, Ioannis N.; Karayannopoulou, Georgia; Theodosiou, Zenonas; Kostopoulos, Ioannis; Bobos, Mattheos; Bevilacqua, Generoso; Aretini, Paolo; Starita, Antonina; Lyroudia, Kleoniki; Pitas, Ioannis (My University, 2008)
HER2-positive breast cancer is characterized by aggressive growth and poor prognosis. Women with metastatic breast cancer with over-expression of HER2 protein or excessive presence of HER2 gene copies are potential candidates for Herceptin (Trastuzumab) targeted treatment that binds to HER2 receptors on tumor cells and inhibits tumor cell growth. Fluorescence in situ hybridization (FISH) is one of the most widely used methods to determine HER2 status. Typically, evaluation of FISH images involves manual counting of FISH signals in multiple images, a time consuming and error prone procedure. Recently, we developed novel software for the automated evaluation of FISH images and, in this study, we present the first testing of this software on images from two separate research clinics. To our knowledge, this is the first concurrent evaluation of any FISH image analysis software in two different clinics. The evaluation shows that the developed FISH image analysis software can accelerate evaluation of HER2 status in most breast cancer cases.
Keywords: Accuracy; Monoclonal antibodies; Antineoplastic agents; Computer interfaces